PENINGKATAN PRODUKTIVITAS DAN MANAJEMEN USAHA BANK SAMPAH SAPU JAGAD KABUPATEN MAGETAN - Syamsul Hadi; Okid Parama Astirin; Suryanto Suryanto; Bambang Sigit Amanto; Setya Nugraha (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Any waste whether it is organic or inorganic waste causes a serious issue that is faced by the Magetan regent. The lack of waste management systems such as uncontrolled garbage accumulation, burning and dumping into rivers and vacant land could lead to pollution. The Solution to solve this issue is the waste bank called Sapu Jagad in Magetan regent which was established in 2015. Sapu Jagad waste bank is also educating and training the people to recycle the waste into a product with an economic value. The product from the waste bank is sold by an online market. However, the production time is sometimes too long since the raw material is not always adequately available. This situation is caused by irregular collection from the community. The result of this activity is the registering process by the waste bank, waste bank fund, and operational bookkeeping using a simple application. Record sales of waste products into crafts and better chairs and tables. The process of storing plastic packaging for drinking water and plastic packaging waste can already be cut into small pieces using a plastic cutting machine which is also invested in a waste bank. Plastic waste storage becomes very space efficient.